Redesign the Forwarding Company's Business Processes Using the Zachman Framework - Bernadus, Gunawan Sudarsono; Andry, Johanes Fernandes; Ranting, Pranchis; Aedah, Abd Rahman (2020)
Forwarding Company is one of the companies in Indonesia that provides delivery services using trucks. To be a company that is far superior to its competitor, the company can implement Information Systems (IS) or Information Technology (IT) that is in line with the vision and mission of its business processes (both activities in the main business processes and activities in supporting business process). Enterprise Architecture Planning or EAP helps make planning for the application of IS / IT that is more mature and better so that implementing IS/IT in the company's business processes can run away and work in accordance with the company's vision and mission. To complement the design of new business processes using EAP, this study will use the Zachman framework adapted to EAP. This framework suggests a logical structure for categorizing, organizing, and describing a detailed picture of a company. Therefore, this research is expected to be able to provide input to companies that are research objectives to execute ARE/IT in conformation with business processes and its vision and mission. Later the results of this study will form a plan about new business processes, both the main and supporting activities that are in accordance with the company based on the Zachman framework.